Experimental Characterization of Ultra-Wideband Channel Parameter Measurements in an Underground Mine - B. Nkakanou; G. Y. Delisle; N. Hakem (Journal of Computer Networks and Communications)
Experimental results for an ultra-wideband (UWB) channel parameters in an underground mining environment over a frequency range of 3 GHz to 10 GHz are reported. The measurements were taken both in LOS and NLOS cases in two different size mine galleries. In the NLOS case, results were acquired for different corridor obstruction angles. The results were obtained during an extensive measurement campaign in the UWB frequency, and the measurement procedure allows both the large- and small-scale parameters such as the path loss exponent, coherence bandwidth, and so forth, to be quantified. The capacity of the UWB channel as a function of the physical depth of the mine gallery has also been recorded for comparison purposes.